Dry-casting : computer simulation, sensitivity analysis, experimental and phenomenological model studies - Krantz, William B. (2013)
A model for the dry-casting process for polymeric membrane formation is generalized to include a broader spectrum of boundary conditions. This model is used to conduct a sensitivity analysis to assess which properties and process parameters are most influential and hence need to be determined most accurately. The model predictions are relatively insensitive to changes in the nonsolvent/polymer and nonsolvent/solvent friction coefficients but moderately sensitive to changes in the solvent/polymer friction coefficient. However, the predictions are very sensitive to changes in the gas-phase mass-transfer coefficient, which needs to be well-characterized and carefully controlled during the dry-casting process. Experimental studies for the water/acetone/cellulose acetate system demonstrate that changes in the boundary conditions can result in dramatically different membrane morphologies. The results of the modeling, sensitivity analysis and experimental studies are used to advance a simple phenomenological model for the dry-casting process that explains all the observed trends. This is used to develop a set of design heuristics for dry-casting based on the effect of changes in the properties and parameters on the casting solution and gas-phase mass-transfer resistances, the solvent concentration at the interface and the mass-transfer rate.